Impact Of The Oil Condition On The Thermography Of Turbocharger Operation (Ciencias de la Ingeniería y Aplicadas, 2025)
In The turbo of a diesel engine reaches very high temperatures during operation, so the role of the lubrication system and in particular the oil is fundamental for its care and performance. The project involves the use of thermography to determine the impact of oil quality on turbo operation, therefore, it is intended to investigate the thermal behavior of a turbocharger in its different work areas under certain operating conditions and how oil influences as a refrigerant in this supercharging system. The maintenance required by this type of elements are expensive, so care in its operation is fundamental, being the purpose of the project to establish the role of the lubricant in the care of the turbocharger, in addition to the incorporation of new tools in the processes of revision of the vehicle such as the thermal camera.
Keywords: Turbocharger; Oil in thermography; incidence of oil condition; thermal behavior of a compressor